Evaluating urban microclimate temperature using Envi-Met Simulation Model: a case study conducted in two city areas, Pudu and Wangsa Maju - Anis Batrisyia Asmadi,; Alamah Misni,; Mohamed Brahimi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Urban areas usually experience the urban heat island effect, where the area is significantly warmer than surrounding rural areas. This is due to the urban character and microclimate change. This study assesses the temperature of urban microclimate characteristics that influence typical urban commercial. The method study uses the ENVI-met numerical simulation software to compare differences in temperature of two urban commercial districts in Pudu and Wangsa Maju. A similar scale was used to simulate these sites with the same climatic conditions. Urban layout, building heights and densities, human movement, landcover, greening, and pavements were discovered to impact temperature change significantly. The variations of simulated and measured temperatures were parabolic in shape, and the variation trends of both were similar. The relative humidity in a residential district declined with increased temperature. The highest temperature is 32.5°C during peak time at 14.00 pm in Pudu, while at Wangsa Maju, peak time is at 13.00 pm with 31.2°C. The results were significantly influenced by the landcover (building, vegetation, and pavement), human movement and urban layout. The height of taller high-rise buildings contributed to the increase in temperature, and densely vegetated areas proved to reduce the temperature in urban areas. The findings of this study will contribute to the future microclimate planning of the cities as well as retrofitting landscaping programs and urban settings, especially in the city's area of Kuala Lumpur.